1996
DOI: 10.1897/1551-5028(1996)015<0782:beopdp>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGICAL EFFECTS OF POLYCHLORINATED DIBENZO-p-DIOXINS, DIBENZOFURANS, AND BIPHENYLS IN BALD EAGLE (HALIAEETUS LEUCOCEPHALUS) CHICKS

Abstract: During the 1992 breeding season, eggs of bald eagles (Haliaeetus leucocephalus) were collected within a gradient of exposure to chlorinated hydrocarbon pollutants, particularly from pulp mill point sources, on the southern coast of British Columbia, Canada. Twenty-five eggs were placed in a laboratory incubator, of which 18 hatched; chicks were sacrificed within 24 h. Hatching success was not significantly different between eggs taken from pulp mill sites and reference sites. A hepatic cytochrome P4501A (CYP1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
57
5
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 35 publications
13
57
5
1
Order By: Relevance
“…Levels of TCDD in osprey eggs collected at the CR/P during this study (geometric mean, 78 pg/g) were higher than levels reported in other avian studies (range, 15-37 pg/g [9,10,14,45,46]) with one exception (211 pg/g in great blue heron eggs [8]). Conversely, eggs from these other avian studies contained levels of coplanar PCBs that were higher than those from the CR/P (range, 31-63 pg/g TCDD-Eq).…”
Section: Susceptibility Of Ospreys To Phhscontrasting
confidence: 76%
“…Levels of TCDD in osprey eggs collected at the CR/P during this study (geometric mean, 78 pg/g) were higher than levels reported in other avian studies (range, 15-37 pg/g [9,10,14,45,46]) with one exception (211 pg/g in great blue heron eggs [8]). Conversely, eggs from these other avian studies contained levels of coplanar PCBs that were higher than those from the CR/P (range, 31-63 pg/g TCDD-Eq).…”
Section: Susceptibility Of Ospreys To Phhscontrasting
confidence: 76%
“…This trend is similar to the observations in common terns from many parts of the world. The observed TEQ values were greater than the Lowest-Observed-Effective-Level (LOEL) for eggs of chickens and wood ducks, and within the ranges of NOEL and LOEL observed for common tern embryos in an egg injection study, and bald eagle embryos in a field study [3,30,44] as shown in Fig. 2.…”
Section: Toxic Thresholdsupporting
confidence: 72%
“…Several studies documented the association between various biological responses and effects with exposure to persistent organic contaminants (POCs) such as dioxin-like polychlorinated biphenyls (dioxin-like PCBs), 2,3,7,8-chlorine substituted polychlorinated dibenzo-p-dioxins (PCDDs), and dibenzofurans (PCDFs) in fish-eating water birds [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Many species of terns (Sterna spp.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murvoll et al (1999) found a borderline significant positive correlation between PCBs in lipid weight and plasma retinol in shag (Phalacrocorax aristotelis) hatchlings, at PCB levels lower than levels in the great blue heron from the St. Lawrence. Murk et al (1994) found increased plasma retinol levels with increasing PCB burden in common tern (Sterna hirundo) hatchlings, while Elliott et al (1996) found no difference in 1-day-old bald eagle chick's plasma retinol among colonies with various levels of dioxin and furan contamination. However, all these results are from very young birds in which absorption of the vitellus at hatching may influence circulating retinol levels.…”
Section: Discussionmentioning
confidence: 98%